KINERJA GURU DALAM PROSES PEMBELAJARAN DI SMP LABSCHOOL UNTAD PALU - Agung, Abdi (Katalogis, 2017)
The research aims to determine the Teacher Performance in the process of learning at junior Labschool UNTAD Palu. Who tried to examine to determine the performance of teachers in the learning process. The data analysis was qualitative descriptiveÂ techniques (Miles Huberman), with the number of informants, ie 7 people. The method used in determining the informant is purposive. Data collection techniques using observation, interviews and documentation. The method used is a qualitative research method. The theory performance used T.R. Mitchell covering aspects of quality of work, quantity of work and knowledge work. The results of this research explained that the performance of teachers in the learning process in Junior Labschool UNTAD Palu, yet all goes well. Three aspects were studied, namely the quality of work, quantity of work and knowledge work. One, two sub aspects of quality are competence and thoroughness less runs in accordance with the standards because of inadequate mastery learning technology, mastery of productive sectors and and less careful in choosing teaching methods. Statutes and neatness goes well. Second, while the sub aspects of the quantity of work teachers in working time and the volume of work has been going well, while the sub aspects of labor productivity is still inadequate because of the lack of teacher participation in scientific forums and teachers' lack of scientific papers. Third, sub aspects of knowledge work of teachers in understanding the procedures and methods of work has been going well.